Gintong Kawayan a proposed multi-faceted Riparian Park along the Meycauayan River Corridor to Mitigate the Industrial Wastewater Pollution in Meycauayan, Bulacan - Villegas, Paolo Miguel S. (College of Architecture, University of the Philippines Diliman, 2025)
The city of Meycauayan is a 1st class component city within Bulacan that is known for its industries like jewelry and leather, but the vast number of industries have led to toxic waste pollution along the Marilao-Meycauayan-Obando River System (MMORS) and the Meycauayan River, which is a health hazard for nearby community members. Its conditions also affect the Manila Bay, a water body of high economic importance in the Philippines. With the knowledge that industrialization is a primary driver for water pollution in the Meycauayan River, the study aims to design a multi-faceted riparian park along the Meycauayan River corridor to mitigate wastewater pollution and improve the water quality of the Meycauayan River. The study analyzed the possible relationship of industries and Meycauayan River water quality through biotope mapping and identification of pollution key points, showing that informal mixed-use zones are the primary contributors of pollution. The possible strategies, technologies, and landscape elements for the park were identified through an ecological evaluation management approach, a key informat interview, and a community survey. The final riparian park design includes water filtration or purification methods, landscape buffers for habitat revival or flood control, and culturally-relevant park systems dedicated to the local community. The study recommends future studies to consider an approach that further involves industries and local government units in both pollution mitigation and initiatives or projects.